Virtual Classroom Sebagai Media Pembelajaran Berbasis Android Pada Ranah Kognitif Dan Penilaian Formatif Mahasiswa Diii Kebidanan Daerah Urban Dan Sub Urban - Triana Rahmiaty; Syafruddin Syarif; Andi Nilawati Usman (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Objective: This study aims to determine the effect of virtual classroom as an Android-based learning media in the cognitive domain and formative assessment of midwifery students in urban and sub-urban areas.Method: This type of research used in this study is a quasi-experimental design (Quasi experiment) taken with a purposive sampling technique on Midwifery Urban and Sub-urban DIII Students in December 2019 - January 2020. The effect was tested using Chi-square.Results: The results of the analysis using the chi-squre test showed no relationship between the use of virtual classroom as an Android-based learning media in the cognitive domain and in the formative assessment of midwifery students in urban and sub-urban areas.Conclusion: The use of virtual classroom as a medium of learning does not affect cognitive abilities and the feasibility of formative assessment.